Studi Molecular Docking dan Farmakoinformatika Senyawa Kurkumin dan Arturmeron pada Tumbuhan Kunyit (Curcuma Longa Linn.) Sebagai Antihipertensi: Molecular Docking and Pharmacoinformatics Study of Curcumin and Arturmeron Compounds in Turmeric Plants (Curcuma Longa Linn.) as Antihypertensive - Agustian, Dede Rahman; Syafrizayanti, Syafrizayanti; Alfath, Yuma Nur; Riga, Riga; Kusnanda, Arif Juliari (Jurnal Sains dan Kesehatan, 2024)
Content Angiotensin Converting Enzyme (ACE) is an enzyme that is able to convert the peptide angiotensin 1 into angiotensin 2 which plays a role in the process that causes hypertension. Curcumin and artumeron are a group of chemical compounds that are widely contained in the turmeric plant (Curcuma Longa Linn.) which are reported to have the potential to inhibit ACE in vitro. The aim of this research is to predict the binding interactions of the curcumin and artumeron compound groups with the amino acids in ACE and using the native ligand captopril as the standard ligand. The method used was pharmacokinetic screening of active compounds in the curcumin and artumeron groups using ADMET predictions, Lipinski Rule of five and molecular docking simulations with the MOE program. Based on the results of screening and molecular docking simulations, it shows that the curcumin compound can bind to the ACE enzyme with a binding affinity of -6.032 kcal.mol-1 with a binding site with the amino acid Leu 342 better than captopril which has a binding affinity value of 4.427 kcal.mol-1 with binding sites with the amino acids Glu 342, Pro 344 and Thr 345. These results showed the curcumin compound potential used as a candidate for natural ingredients in antihypertensive treatment because according to in silico predictions it has abilities that are not much different from captopril. Keywords:          ACE, antihypertensive, in silico, Curcuma Longa Linn.   Abstrak Angiotensin Converting Enzyme (ACE) merupakan enzim yang mampu merubah peptida angiotensin 1 menjadi angiotensin 2 yang berperan dalam proses penyebab hipertensi. Senyawa kurkumin dan artumeron merupakan golnngan senyawa kimia yang banyak terkandung dalam tumbuhan Kunyit (Curcuma Longa Linn.) dilaporkan mempunyai potensi dalam menghambat ACE secara in vitro. Tujuan penelitian ini adalah untuk prediksi interaksi penambatan golongan senyawa kurkumin dan artumeron  dengan asam-asam amino pada ACE dan menggunakan ligan native kaptopril sebagai ligan standarnya. Metode yang digunakan berupa skrining senyawa aktif golongan kurkumin dan artumeron secara farmakokinetika dengan prediksi ADMET, Lipinski Rule of Five dan simulasi penambatan molekul dengan program MOE. Berdasarkan hasil skrining dan simulasi penambatan molekul menunjukkan bahwa senyawa curcumin dapat berikatan dengan enzim ACE dengan afinitas pengikatan sebesar -6,032 kcal.mol-1 dengan situs pengikatan dengan asam amino Leu 342 lebih baik dibandingkan dengan captopril yang mempunyai nilai afinitas pengikatan sebesar 4,427 kcal.mol-1 dengan situs pengikatan dengan asam amino Glu 342, Pro 344 dan Thr 345. Hasil ini menunjukkan senyawa curcumin  dapat dijadikan sebagai kandidat bahan alami dalam pengobatan antihipertensi karena secara prediksi in silico memiliki kemampuan yang tidak berbeda jauh dengan kaptopril. Kata Kunci:         ACE, antihipertensi, in silico, Curcuma Longa Linn.